Bio-mediated CN cycling in serpentinites and the origin of life - S. Tenuta; K. A. Evans; S. M. Reddy; B. M. Tutolo; W. D. A. Rickard; D. W. Saxey (Scientific Reports)
Abstract Hydrogen-rich, high pH conditions associated with serpentinisation are fundamental to some theories of the origin of life on Earth and other planets. In these theories, the first life formed in hydrothermal vents from organic compounds produced by metal-catalysed reduction of carbon dioxide and nitrate by hydrogen. Competing theories suggest that life could not have arisen without hydrogen cyanide (HCN), and that HCN was provided by vaporisation of large impactors. Here, we show that carbon- and nitrogen-bearing species are associated with chalcopyrite and native copper in serpentinised peridotite from the Wadi Tayin Ophiolite, Oman. We propose a model in which serpentinisation produces hydrogen that reduces copper in chalcopyrite to form native copper, and reduces oxidised carbon and nitrogen to form reduced carbon and nitrogen. In this model, reduction of carbon and nitrogen is catalysed by copper, and previously undocumented nanolayers of silver within metallic copper may enhance catalytic properties in natural systems. Microbial involvement is consistent with microstructural observations, documented microbial activity and isotopic data within the Wadi Tayin Ophiolite. However, similar features can form abiotically. Our discovery establishes spatial links among components believed to have supported the emergence of life. Further, mineral-hosted CN-species provide a previously unconsidered reservoir of nitrogen within serpentinites, which may deliver nitrogen to the deep mantle via subduction.